Analisis Fundamental Makro Dan Fundamental Mikro Terhadap Nilai Perusahaan Dengan Struktur Modal, Karakteristik Perusahaan, Kinerja Keuangan Sebagai Variabel Intervening Pada Perusahaan Jasa Yang Terdaftar Di Bursa Efek Indonesia - Aprilia Wahana Putri; Hwihanus (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The aim of this research is to analyze whether there is an influence of Macro Fundamental Analysis, Micro Fundamental Analysis on Company Value with Capital Structure, Company Characteristics and Financial Performance in Service Companies Listed on the Indonesian Stock Exchange in 2019-2023. This research uses quantitative research and the type of data used is secondary data obtained from the results of annual reports of companies listed on the Indonesia Stock Exchange (BEI) for 2019-2023 through the official website of the Indonesia Stock Exchange and other supporting journals related to this research. . The sample used in this research consisted of 6 financial services companies listed on the Indonesia Stock Exchange, whose data were then analyzed using the Smart-PLS version 4 application. The results of this research show that among the proposed hypotheses there are 7 independent variables that have a positive and significant effect on the variables dependent, while the remaining 6 variables have a negative effect on the dependent variable, namely company value